La península de los volcanes - Hervé, Francisco, 1971-; Brahm, Sebastián; Vásquez, Agustín (Panchito Films, 2004)
The dreams, aspirations and educational opportunites of four Chilean young women are compared. Two of the young women study to be textile technicians in a public industrial school in Santiago's San Joaquin commune. Their dreams of the future include families, further study and a chance to improve their social and economical situation. They are contrasted against two others of the same age who study at the exclusive Saint George's School where they prepare to attend university and develop themselves through art and music.